Pengaruh Implementasi Teori Motivasi Hierarki Abraham Maslow Dalam Peningkatan Semangat Kerja Karyawan PT. Nutrihub - Dhita Adriani Rangkuti; adarman ndruru; Sani Eldima Nopelia saragih; Irma Mediana Saruli Simanjuntak (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the implementation of Abraham Maslow's Hierarchical Motivation Theory in increasing employee morale at PT. Nutrihub. The independent variables used in this study are self-actualization needs, esteem needs, social needs, safety needs, and physiological needs. The dependent variable is employee morale. The population in this study are employees of PT. Nutrihub. The sampling technique used was a saturated sample technique with a total sample of 76 employees. For data analysis carried out with validity and reliability tests, descriptive statistical tests, classical assumption tests, multiple regression analysis tests, tests determination, f test and t test. The results showed that the variables of self-actualization needs, esteem needs, social needs, safety needs, and physiological needs partially had a positive and significant effect on the morale of Nutrihub employees. The implications of this research are the basis for companies to see the effect of self-actualization, appreciation, social, security, physiology and employee morale and contribute to improving learning in students of the Faculty of Economics. Keywords: Self-Actualization Needs, Appreciation Needs, Social Needs, Security Needs, Physiological Needs, Employee Morale